Diurnal fluctuations of ozone concentrations and its precursors and prediction of ozone using multiple linear regressions - Nor Azam Ramli,; Nurul Adyani Ghazali,; Ahmad Shukri Yahaya, (Environmental Management Society, Malaysia, 2010)
The chemical reaction of pollutants emitted into the atmosphere leads to a variety of oxidized products, which are commonly referred to as secondary pollutants. Ground level ozone is a known secondary photochemical pollutant of major importance possessing detrimental effects on health, agriculture, natural/urban ecosystems and materials. Ozone (O3) can irritate lung airways and cause inflammation much like sunburn. Hourly and monthly variations of O3 and their precursors – nitrogen oxides (NOx) and meteorological parameters (temperature and wind speed) were presented using time series plots. Possibility of employing multiple linear regression models as a tool for prediction of O3 concentration was also tested. Measurement was performed continuously in 2005 at two sampling stations located in the metropolitan area of Malaysia. Results indicated that the formation of O3 in the study area was influenced by NOx precursors and meteorological conditions. The hourly variation showed maximum O3 concentrations were recorded between 1300 to 1400 hours, while NOx and nitrogen dioxide (NO2) exhibited two maxima, at 0800-1000 and 2000-2100 hours. The daily cycle of highest O3 concentrations were revealed a lower night level and inverse relations between O3 and NOx. This is clear evidence of photochemical formation of O3. Temperature has the highest influence to the high O3 concentrations